Construction of environment-friendly core-shell ammonium perchlorate@1,3,5-triamino-2,4,6-trinitrobenzene composites with high safety and excellent thermal decomposition properties - Ping Ye; Pengfei Xu; Hao Guo; Bing Gao; Guangcheng Yang; Bing Huang; Changping Guo (Materials & Design, 2020)
Modern solid propellants integrated with enviro-friendly, high safety and excellent thermal decomposition properties are highly desired in the aerospace as well as weapon areas, and it also presents significant challenging. For this purpose, a simple ultrasonic synthesis method was proposed to 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) nanoparticles were deposited on the surface of ammonium perchlorate (AP) to obtain core-shell AP@TATB. Since there is no heavy metal involved in the composite, it can effectively avoid the pollution of heavy metals to the environment. The prepared samples were analyzed by powder X-ray diffraction (XRD), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS), it has been confirmed that a uniform and complete shell TATB was formed on the surface of AP particles when the content of TATB was 10%, differential scanning calorimetry (DSC) data shows that the shell TATB effectively reduces the high-temperature decomposition (HTD) of AP and significantly increases heat release of AP by 2.67 times. In addition, AP@TATB also showed excellent safety in the sensitivity test. The ease of the synthesis method and the promising feature of the obtained composites exhibit great potential for application in environment-friendly modern solid propellants.